Metal-free B-B dehydrocoupling reaction of a simple borane adduct: convenient access to a nucleophilic diborane(4) - Kistner, Lucas; Sigmund, Lukas M.; Grieser, Fabian Frank; Krauss, Julian; Leingang, Simone; Kaifer, Elisabeth; Greb, Lutz; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2024)
The selective formation of homonuclear bonds is of key importance in synthetic chemistry. Especially, dehydrocoupling reactions are attractive as ecologically and economically friendly alternatives to established reductive bond forming reactions, since they do not require the use of stoichiometric amounts of a reducing reagent and produce only valuable dihydrogen as by-product. Here, we report on a metal-free B-B dehydrocoupling reaction that starts directly from a simple, easily accessible BH3 adduct, providing convenient access to a new nucleophilic dihydridodiborane in excellent yield. The dihydridodiborane in turn activates dihydrogen, allowing to obtain quantitatively the dideuteridodiborane from the dihydridodiborane by D2 activation. On the basis of detailed quantum-chemical calculations, the mechanism of this unprecedented reaction is elucidated. Some key points that are essential for metal-free dehydrocoupling are disclosed, paving the way for their systematic evaluation and application. Generally, the formation of a B-B bond is accomplished by reduction of a haloborane. Here, we report a metal-free B-B dehydrocoupling reaction starting with a simple, readily available borane adduct. A detailed mechanistical examination paves the way for a rational approach to thermal B-B dehydrocoupling reactions.image
Gesehen am 03.05.2024